Population Growth and the Tragedy of the Commons: Can Trade Prevent Natural Resource and Welfare Collapse? - Maurice Schiff (Global Labor Organization (GLO), 2024)
Many developing countries depend crucially on open-access renewable natural resources (NR). Trade is generally viewed as hurting the long-term health of NR in commodity-exporting countries. I examine whether trade might be beneficial in the case of population growth. Dynamic general equilibrium NR models have typically assumed constant return to scale in the manufacturing sector. I examine trade's impact under constant, decreasing and increasing returns. While population growth always results in NR and welfare collapse under autarky, the impact under trade depends critically on the manufacturing sector's returns-to-scale technology. Under trade, NR and welfare are unaffected by population growth under constant returns, collapse under decreasing returns, and increase under increasing returns. Empirical studies have typically found constant or increasing returns. Thus, countries experiencing rapid population growth may obtain long-term benefits from opening up to trade, though they experience short-term NR costs.
Keywords: D62; F18; Q22; Q27; Q56; 330; Population growth; Renewable natural resources (NR); Trade vs autarky; NR and welfare or societal collapse